International Topical Meeting on Microwave Photonics. MWP'99. Technical Digest (Cat. No.99EX301)
DOI: 10.1109/mwp.1999.819642
|View full text |Cite
|
Sign up to set email alerts
|

Fabry-Perot type resonantly enhanced Mach-Zehnder modulator

Abstract: A novel resonantly enhanced Mach-Zehnder modulator with 10 dE3 enhancement in link performance is demonstrated. Enhancement is achieved through placement of the electrode structure within a Fabry-Perot type cavity. Theoretical prediction and experimental verification are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In this section, we use the model in Section II to synthesize an optimized RE-MZM device [5], [20]. This RE-MZM has been fabricated and characterized, and the numerical model is validated through comparison with measurements.…”
Section: Synthesis Of An Optimized Re-mzm Devicementioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we use the model in Section II to synthesize an optimized RE-MZM device [5], [20]. This RE-MZM has been fabricated and characterized, and the numerical model is validated through comparison with measurements.…”
Section: Synthesis Of An Optimized Re-mzm Devicementioning
confidence: 99%
“…Several narrow bandwidth optical modulators have been proposed in the literature to provide improved modulation efficiency at the expense of bandwidth. This are called resonantly enhanced Mach-Zehnder modulators (RE-MZMs) [5]- [9]. A few examples of RE-MZMs where optical resonators are used have been reported [10].…”
Section: Introductionmentioning
confidence: 99%
“…Inductive terminations In Fabry-Perot type RE-MZMs [9], the lengths of the resonant cavities are slightly less than a multiple of half of wavelength. At high frequencies, the wavelengths of the microwave signals are very short.…”
Section: Rf Inmentioning
confidence: 99%
“…To realize broadband E-O conversion, external modulation using Mach-Zehnder (MZM) and electroabsorption modulators (EAMs) have already been demonstrated [6,7]. In addition, it has recently been shown that the use of resonant enhancement and the optimization of modulators for analog applications can lead to modulators having both low cost and high conversion efficiency [8]. [12].…”
Section: Fiber Wireless Systemsmentioning
confidence: 99%